FIELD EXPERIENCE REPORT: TAMMY WALKER CANCER CENTER - Byquist, Bridget (My University, 2017)
My public health field experience at Tammy Walker Cancer Center at Salina Regional Health Center in Salina, Kansas was completed in July and August of 2013. Under the supervision and direction of Linda Hinnenkamp, RN, I completed 240 hours of experience. Ms. Hinnenkamp is the cancer outreach coordinator at Tammy Walker Cancer Center (TWCC) and is responsible for planning many local outreach and public health events in Salina and the surrounding region, often in partnership with other local organizations. In addition, she coordinates cancer survivor events and support groups and oversees the Breast Cancer Awareness Program at TWCC, which works in fifteen counties in north central Kansas to educate women about the importance of breast cancer screening and refers women for free and low-cost mammograms. During my time at TWCC, I had the opportunity to work on several different projects and help plan several public health events. I served on two planning committees: one for free cancer screening events and the other for an educational workshop and seminar for middle school girls co-sponsored by TWCC and the local school district (USD 305). I also conducted a written survey of cancer survivors in the local community to assess their needs and the adequacy of current support services. Based on the survey, I made recommendations for improvement of survivor events and support services at TWCC. I also produced two public reports describing the demographics and characteristics of the patients served by TWCC and assisted in the annual reapplication process for the Avon Breast Cancer grant.
Keywords: Tammy Walker Cancer Center; Salina Regional Health Center; Cancer prevention; Nutrition Education; Cancer Survivorship; Breast Cancer Awareness